Relational Lattices: From Databases to Universal Algebra - Litak, Tadeusz Michal; Mikulás, Szabolcs; Hidders, Jan (Journal of Logical and Algebraic Methods in Programming, 2016)
Relational lattices are obtained by interpreting lattice connectives as natural join and inner union between database relations. Our study of their equational theory reveals that the variety generated by relational lattices has not been discussed in the existing literature. Furthermore, we show that addition of just the header constant to the lattice signature leads to undecidability of the quasiequational theory. Nevertheless, we also demonstrate that relational lattices are not as intangible as one may fear: for example, they do form a pseudoelementary class. We also apply the tools of Formal Concept Analysis and investigate the structure of relational lattices via their standard contexts. Furthermore, we show that the addition of typing rules and singleton constants allows a direct comparison with the monotonic relational expressions of Sagiv and Yannakakis.<br
UnivIS-Import:2016-06-01:Pub.2015.tech.IMMD.profes_1.relati
Keywords: Relational lattices; Relational algebra; Database theory; Algebraic logic; Lattice theory